The Numbers Game: Exploring Everyday Math Applications - Khurt Marcellin Rosell; Rey Anthony Baylon; Jherome Abellera; Evan P. Taja-on (PT FORMOSA CENDEKIA GLOBAL, 2025)
Mathematics is essential in everyday life and the modern world, yet its theoretical study in classrooms often needs more practical application, creating a gap in understanding. This study aims to bridge the gap between theoretical mathematics and real-world problem-solving by exploring how mathematical concepts can be applied in everyday life by everyday people. The study used a phenomenological research design and purposive sampling to explore the everyday applications of mathematics, interviewing 11 individuals from diverse backgrounds in Malaybalay City. The study reveals that mathematics is deeply embedded in everyday and professional activities and learned through authentic engagement. The result underscores the importance of contextualizing mathematical concepts to make them relevant and meaningful. Furthermore, the result emphasizes the need for an inclusive approach to mathematics education that integrates universal, practical, and culturally specific dimensions